PENGARUH PENATAAN RUANG KANTOR MADRASAH TERHADAP KUALITAS PELAYANAN KETATAUSAHAAN - Musdalifah, Sri; Zakaria, Zakaria; Dewantara, Andi Harpeni (DIDAKTIKA, 2022)
This study aims to investigate the effect of the space arrangement toward administrative services at MTS DDI Walimpong, Soppeng Regency, Indonesia. This is a quantitative research using questionnaire as instrument to collect the data. This study involved a staff of administrative office and 35 students. Data were analyzed by using formula of proportion and product moment correlation, as well as testing the independence between two factors using simple linear regression test statistics. Findings of this study indicate that the spatial arrangement of the madrasah office at MTS DDI Walimpong, Soppeng Regency is quite good. The average respondent's answer is 50.61 which is in the fairly good category. Meanwhile, the administrative services at MTS DDI Walimpong, Soppeng Regency, are quite good. The average of respondents' answers is 53.94 which is in the good enough category. Based on the results of the ANOVA test, the Fcount value of 10.14376653>Ftable of 4.130017699, and the T-test of 3.10485017186>Ttable of 1.369709548. This shows that there is a positive and significant influence on the arrangement of madrasah office space on the improvement of administrative services. Â Keywords: office space arrangement, service, administration. Â